1995
DOI: 10.1021/bi00044a015
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Dihydroxybenzenes with the Ca2+-ATPase: Separate Binding Sites for Dihydroxybenzenes and Sesquiterpene Lactones

Abstract: The Ca(2+)-ATPase of skeletal muscle sarcoplasmic reticulum is inhibited by 2,5-di-tert-butyl-1,4-dihydroxybenzene (BHQ) and other hydrophobic 1,4-dihydroxybenzenes. Inhibitory potency increases on increasing substituent chain length from 2,5-dipropyl-1,4-dihydroxybenzene to 2,5-di-tert-amyl-1,4-dihydroxybenzene, the most potent inhibitor, but then decreases for 2,5-bis(7-methylheptyl)-1,4-dihydroxybenzene. Kinetic measurements are consistent with isomerization following the initial binding of BHQ to the ATPas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 29 publications
5
44
0
Order By: Relevance
“…Kinetic studies indicate that although inhibition by a variety of hydrophobic molecules is generally related to interference with global conformational changes of the enzyme (38), TG and DBHQ may actually bind to separate sites (39). We then tested whether the F256V mutation would interfere with the inhibitory effect of DBHQ.…”
Section: Tg Interferes With Conformationalmentioning
confidence: 99%
“…Kinetic studies indicate that although inhibition by a variety of hydrophobic molecules is generally related to interference with global conformational changes of the enzyme (38), TG and DBHQ may actually bind to separate sites (39). We then tested whether the F256V mutation would interfere with the inhibitory effect of DBHQ.…”
Section: Tg Interferes With Conformationalmentioning
confidence: 99%
“…By far the best known and most potent inhibitor is thapsigargin (TG), a plant sesquiterpene lactone (18), with the dissociation constant in the subnanomolar range (15). Another commonly used inhibitor is 2,5-di-tert-butyl-1,4-dihydroxybenzene (BHQ), an antioxidant, which has a much simpler chemical structure and a lower affinity (19). We have determined the crystal structures of the ATPase with either one [E2(TG) or E2(BHQ)] or both [E2(TGϩBHQ)] of them bound (4,13).…”
mentioning
confidence: 99%
“…1, a series of four 2,5-disubstituted hydroquinones with cyclic substituents was synthesized by Friedel-Crafts alkylation of hydroquinone with commercially available cyclic tertiary alcohols. Since previous studies had shown that the most active hydroquinone-based SERCA inhibitors with non-cyclic residues carried between four and six carbon atoms in their side chains [10], [13], we varied the ring size of the newly synthesized compounds from four to seven carbon atoms to be within this size range. Disubstituted hydroquinones 1-4 were prepared in low yields by small scale (100-200 mg) reaction of hydroquinone with slightly more than two equivalents of the appropriate cycloalkanol under acidic conditions.…”
Section: A Synthesis Of 25-disubstituted Hydroquinonesmentioning
confidence: 99%
“…The observed trend suggested an optimum number of six carbon atoms total (five ring plus one methyl carbon atom) in the substituent, a size which is most likely dictated by the size of the binding pocket. It should be noted that 4 is about as potent as the most active non-cyclic hydroquinone-based SERCA inhibitor known to date, 2,5-diamylhydroquinone (IC 50 : 0.34 M) [10], [29]. …”
Section: A Synthesis Of 25-disubstituted Hydroquinonesmentioning
confidence: 99%
See 1 more Smart Citation